Histone signature of metanephric mesenchyme cell lines - McLaughlin, Nathan (Landes Bioscience, 2013)
The metanephric mesenchyme (MM) gives rise to nephrons, the filtering units of the mature kidney. The MM is composed of uninduced (Six2(high)/Lhx1(low)) and induced (Wnt-stimulated, Six2(low)/Lhx1(high)) cells. The global epigenetic state of MM cells is unknown, partly due to technical difficulty in isolating sufficient numbers of homogenous cell populations. We therefore took advantage of two mouse clonal cell lines representing the uninduced (mK3) and induced (mK4) metanephric mesenchyme (based on gene expression profiles and ability to induce branching of ureteric bud). ChIP-Seq revealed that whereas H3K4me3 active region “peaks” are enriched in metabolic genes, H3K27me3 peaks decorate mesenchyme and epithelial cell fate commitment genes. In uninduced mK3 cells, promoters of “stemness” genes (e.g., Six2, Osr1) are enriched with H3K4me3 peaks; these are lost in induced mK4 cells. ChIP-qPCR confirmed this finding and further demonstrated that G9a/H3K9me2 occupy the promoter region of Six2 in induced cells, consistent with the inactive state of transcription. Conversely, genes that mark the induced epithelialized state (e.g., Lhx1, Pax8), transition from a non-permissive to an active chromatin signature in mK3 vs. mK4 cells, respectively. Importantly, stimulation of Wnt signaling in uninduced mK3 cells provokes an active chromatin state (high H3K4me3, low H3K27me3), recruitment of β-catenin, and loss of pre-bound histone methyltransferase Ezh2 in silent induced genes followed by activation of transcription. We conclude that the chromatin signature of uninduced and induced cells correlates strongly with their gene expression states, suggesting a role of chromatin-based mechanisms in MM cell fate.